2013
DOI: 10.4081/mrm.2013.578
|View full text |Cite
|
Sign up to set email alerts
|

Erectile dysfunction and sex hormone changes in chronic obstructive pulmonary disease patients

Abstract: Background: The prevalence of sexual dysfunction in patients with COPD is high and its significance has not been sufficiently stressed. The aim of this study is to investigate the incidence of erectile dysfunction (ED) and the factors affecting its frequency in COPD patients. Methods: Seventy patients with COPD and 68 healthy volunteers were included in the study. The International Index of Erectile Function questionnaire was used to evaluate ED, and the Beck Depression Inventory was used to evaluate depressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
14
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 21 publications
4
14
0
3
Order By: Relevance
“…Consistent with this, increased daytime sleepiness, decreased total sleep time, decreased sleep efficiency, and levels of fatigue have been reported during an exacerbation [54,55]. In addition, COPD has previously been associated with sexual dysfunction in males, particularly erectile dysfunction, with most patients dissatisfied with their current and expected sexual function [56,57]. How COPD exacerbations affect sexual functioning has not yet been fully elucidated, but sex hormone levels have been shown to be markedly altered during a COPD exacerbation [58], which may have resulted in sexual dysfunction.…”
Section: Effect On Quality Of Life and Physical Activitysupporting
confidence: 57%
“…Consistent with this, increased daytime sleepiness, decreased total sleep time, decreased sleep efficiency, and levels of fatigue have been reported during an exacerbation [54,55]. In addition, COPD has previously been associated with sexual dysfunction in males, particularly erectile dysfunction, with most patients dissatisfied with their current and expected sexual function [56,57]. How COPD exacerbations affect sexual functioning has not yet been fully elucidated, but sex hormone levels have been shown to be markedly altered during a COPD exacerbation [58], which may have resulted in sexual dysfunction.…”
Section: Effect On Quality Of Life and Physical Activitysupporting
confidence: 57%
“…In addition, a direct correlation between testosterone level and the severity of COPD has been observed (Vertkin, 2013). In a study comprising 70 patients with COPD, prevalent erectile dysfunction and lower testosterone level were observed, but the difference in testosterone level was not statistically significant compared with the control group (Kahraman et al, 2013). Metaanalysis of 2918 patients in nine studies involving patients with COPD, testosterone concentration was lower than in control groups.…”
Section: Discussionmentioning
confidence: 88%
“…Most (80%) of those with COPD had problems with their erections, whist the rate in those without a COPD diagnosis was 56%. 7 In a later article by Shen et al, over 29,000 males with COPD age and index year matched with the controls found the incidence of ED was 1.88-fold higher in the COPD population, but they had more prevalent morbidities such as diabetes, depression and anxiety, and poor control of COPD was a key factor in ED development so those with more emergency visits and admissions were more likely to have ED. 2 In this issue, Turan et al remind us that sexual problems, inclusive of ED are not commonly addressed by health professionals.…”
mentioning
confidence: 97%